Obinutuzumab-induced b cell depletion reduces spinal cord pathology in a cd20 double transgenic mouse model of multiple sclerosis - Breakell, Thomas; Tacke, Sabine; Schropp, Verena; Zetterberg, Henrik; Blennow, Kaj; Urich, Eduard; Kürten, Stefanie (International Journal of Molecular Sciences, 2020)
B cell-depleting therapies have recently proven to be clinically highly successful in the treatment of multiple sclerosis (MS). This study aimed to determine the effects of the novel type II anti-human CD20 (huCD20) monoclonal antibody (mAb) obinutuzumab (OBZ) on spinal cord degeneration in a B cell-dependent mouse model of MS. Double transgenic huCD20xHIGR3 (CD20dbtg) mice, which express human CD20, were immunised with the myelin fusion protein MP4 to induce experimental autoimmune encephalomyelitis (EAE). Both light and electron microscopy were used to assess myelination and axonal pathology in mice treated with OBZ during chronic EAE. Furthermore, the effects of the already established murine anti-CD20 antibody 18B12 were assessed in C57BL/6 wild-type (wt) mice. In both models (18B12/wt and OBZ/CD20dbtg) anti-CD20 treatment significantly diminished the extent of spinal cord pathology. While 18B12 treatment mainly reduced the extent of axonal pathology, a significant decrease in demyelination and increase in remyelination were additionally observed in OBZ-treated mice. Hence, the data suggest that OBZ could have neuroprotective effects on the CNS, setting the drug apart from the currently available type I anti-CD20 antibodies.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Anti-CD20; B cells; EAE; MAb; Multiple sclerosis; Neurodegeneration; Obinutuzumab